2016
DOI: 10.1111/josh.12418
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the PAQ‐C Questionnaire to Assess Physical Activity in Children

Abstract: PAQ-C had a high reliability but a questionable validity for assessing total PA and MVPA in Spanish children. Therefore, PA measurement in children should not be limited only to self-report measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 42 publications
8
58
0
8
Order By: Relevance
“…This result is in agreement with the Senegalese study which confirmed that the two methods of PA level assessment (accelerometer and PAQ-C) classify school children differently [26]. A Spanish study reported a low correlation (r = 0.228-0.278, p < 0.05) between PAQ-C and accelerometry [13].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result is in agreement with the Senegalese study which confirmed that the two methods of PA level assessment (accelerometer and PAQ-C) classify school children differently [26]. A Spanish study reported a low correlation (r = 0.228-0.278, p < 0.05) between PAQ-C and accelerometry [13].…”
Section: Discussionsupporting
confidence: 80%
“…The most accurate method for measuring energy expenditure during PA, such as doubly labeled water or indirect calorimetry are complex, time-consuming, expensive and impractical when evaluating large populations [13]. Accelerometers are relatively inexpensive objective methods for assessing PA and are increasingly used in PA research [14].…”
Section: Physical Activity Level Assessed By Accelerometer and Paq-c mentioning
confidence: 99%
“…These findings are encouraging: our coefficients comparing the PAQ with accelerometry are notably higher than those in original validation studies in healthy Canadian children ( r = 0.33 and r = 0.39) [12,13]. Our validity results are comparable or superior compared with other validation studies in international samples, such as validation studies in UK versions of the PAQ (total physical activity: r = 0.42, MVPA: r = 0.39) [10], in a Chinese sample (MVPA r = 0.33) [18], two Spanish samples (total physical activity: rho = 0.39, MVPA: rho = 0.34) [14] and (MVPA rho = 0.23) [33], and an Italian sample (MVPA rho = 0.30) [17]. The latter Italian study included a sub-study of reliability and construct validity in children with CHD (with favourable results), but the CHD children were not included in the assessment of criterion validity [17].…”
Section: Discussionmentioning
confidence: 99%
“…One study assessed the reliability between the PAQ-C and PAQ-A version over a 2-year period, and reported weaker but significant associations over time ( rho = 0.30–0.39) [11]. Another study assessed the reliability on the same day a few hours apart, and expectedly found very high reliability coefficients (0.96) [33]. It is important to interpret the strength of a reliability coefficient in relation to the time interval over which the instrument was administered: the very strong coefficients over very short time intervals are desired and encouraging as they support the notion that the wording and design of the instrument elicits consistent responses from children in relation to their recall ability, while a longer time period is indicative of the fact that the instrument is able to capture a relatively stable ‘ranking’ of individuals’ physical activity over time.…”
Section: Discussionmentioning
confidence: 99%
“…The PAQ -C is a valid and reliable self-reported, 7-day recall measure of physical activity in children (18)(19)(20). The PAQ-C was used for all participants enrolled in this study irrespective of age, as it aligns with the typical daily activity schedule within the Australian school system (19).…”
Section: Physical Activity Questionnaire -Child (Paq-c)mentioning
confidence: 99%